(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2024)
Helen Keller, the small deaf-blind girl who defied huge odds, is still widely known more than thirty years after her death. Beyond this public image, though, is the true narrative of a genuine woman: a long-lived writer, socialist, suffragette, and radical activist who is always seen as a child by the public. This essay explores the development of Keller’s enduring legendary position and popular image, examining their goals and contemporary consequences for persons with disabilities. Additionally, it reveals her life’s real story and demonstrates the current problems she encountered. Lastly, it discusses the value of going over her life story again and its importance in promoting disability culture. I recall an assembly at my old school with the topic being "heroes throughout time." With 150 other kids seated cross-legged in the large school hall, we prayed to God for Helen Keller to be brought out there, hoping and praying that we would have the same strength and courage to face life. Maybe we saw The Miracle Worker because, even now, 25 years later, I can’t seem to get rid of a scene from the movie: the young Helen and her instructor, the dramatic scene by the water pump, the moment when Helen, who is blind and deaf, learns to speak and a "miracle" happens.